Factors influencing parent-child relationships in chinese nurses: a cross-sectional study - Lei Huang; Xia Huang; Jingjun Wang; Fengjian Zhang; Yang Fei; Jie Tang; Ya Wang (BMC, 2023)
Abstract Background With the development of the social economy, the effective coordination of the conflict between work and family has become an urgent problem for most parents. Such conflicts are especially acute in the families of nurses with children. Therefore, a timely understanding of the status quo of the parent-child relationship and associated risk factors among nurses will assist in improving their family harmony and the healthy growth of their children. Methods A total of 350 nurses with children at a general tertiary hospital in Sichuan Province, China, were interviewed using a structured questionnaire between June 23 and July 9, 2022. The results were analyzed by multiple linear regression using the stepwise method. Results The results showed that the parent-child relationship received a middle-level mean score of 77.74 (SD = 10.77). The factors that influenced the parent-child relationship among nurses included the parents' character type (β = 0.143, P = 0.002), feeling tired due to dealing with patients (β=-0.150, P = 0.002), the nurse-patient relationship (β = 0.137, P = 0.004), the age of older children (β=-0.153, P = 0.001), number of children (β=-0.093, P = 0.041), sleep quality (β = 0.116, P = 0.014), and family adaptability (β = 0.308, P = 0.000); these factors accounted for 31.3% of the variance in parent-child relationships among nurses. Conclusion The findings of this study will help policy makers and nursing managers to better understand parent-child relationships in Chinese nurses. The results highlighted the importance of the creation of a family-oriented work environment while paying more attention to the parent-child relationships of nurses who are introverted and have more or older children. After busy workdays, nurses should also be encouraged to participate more in family decision-making and strategic parent-child interactions to avoid negative effects on children caused by work-related emotional exhaustion, physical and mental fatigue, and other reasons. The development of good parent-child relationships may help maintain both their and their children's mental health while enhancing their enthusiasm for work and their professional identity.